CLASSIFIERS OF BODO AND KOCH RABHA LANGUAGES - Basumatary, Bindu; Boro, Indira (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The use of classifiers is a significant linguistic feature in many Sino-Tibetan and Tibeto-Burman languages, including Bodo and Koch Rabha languages spoken in North East India, mainly in Assam. Basically classifiers are grammatical elements used with numerals and numbers or quantifiers to categorize and quantify nouns based on their inherent characteristics such as shape, size or function. This abstract explores in Bodo and Koch Rabha languages, highlighting their similarities and unique aspects within the two linguistic systems. with the comparative methods of study.